2015
DOI: 10.1024/0301-1526/a000447
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia and risk of VTE recurrence according to the age at the time of first VTE manifestation

Abstract: Our data do not support a preference of younger patients for thrombophilia testing after a first venous thromboembolic event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…We abstracted the following patient baseline variables that have previously been described as predictors of venous thromboembolism recurrence from our database: age, 3,4 male sex, 3,5 obesity (defined as BMI ≥30kg/m 2 ), 4 localization of index venous thromboembolism (pulmonary embolism, proximal deep vein thrombosis, distal deep vein thrombosis), 6,7 type of index venous thromboembolism (provoked, unprovoked, cancer-related), 3,8 prior venous thromboembolism, 9 family history of venous thromboembolism, 10 inflammatory bowel disease, 11 chronic heart failure, 12 leg paresis (hemiparesis, hemiplegia, paraplegia), 13 varicose vein surgery (a proxy for varicose veins), 4 D-dimer levels at baseline, 14 and thrombophilia (factor V Leiden or prothrombin G20210A mutation). 10,15 Provoked venous thromboembolism was defined as venous thromboembolism following major surgery, estrogen therapy or immobilization (bed rest for more than 72 hours, travel in a sitting position for more than six hours, fracture or a cast of the lower extremity) during the last three months.…”
Section: Predictors Of Recurrent Vtementioning
confidence: 99%
See 1 more Smart Citation
“…We abstracted the following patient baseline variables that have previously been described as predictors of venous thromboembolism recurrence from our database: age, 3,4 male sex, 3,5 obesity (defined as BMI ≥30kg/m 2 ), 4 localization of index venous thromboembolism (pulmonary embolism, proximal deep vein thrombosis, distal deep vein thrombosis), 6,7 type of index venous thromboembolism (provoked, unprovoked, cancer-related), 3,8 prior venous thromboembolism, 9 family history of venous thromboembolism, 10 inflammatory bowel disease, 11 chronic heart failure, 12 leg paresis (hemiparesis, hemiplegia, paraplegia), 13 varicose vein surgery (a proxy for varicose veins), 4 D-dimer levels at baseline, 14 and thrombophilia (factor V Leiden or prothrombin G20210A mutation). 10,15 Provoked venous thromboembolism was defined as venous thromboembolism following major surgery, estrogen therapy or immobilization (bed rest for more than 72 hours, travel in a sitting position for more than six hours, fracture or a cast of the lower extremity) during the last three months.…”
Section: Predictors Of Recurrent Vtementioning
confidence: 99%
“…1 As venous thromboembolism tends to recur, 2,3 the risk of recurrence is an important determinant of the duration of anticoagulant therapy. Several patient characteristics are associated with recurrent venous thromboembolism, including age, 3,4 male sex, 3,5 obesity, 4 localization of venous thromboembolism, 6,7 unprovoked venous thromboembolism, 3,8 cancer-related venous thromboembolism, 2,3 prior venous thromboembolism, 9 family history of venous thromboembolism, 10 inflammatory bowel disease, 11 chronic heart failure, 12 leg paresis, 13 varicose veins, 4 elevated D-dimer at baseline, 14 or thrombophilia. 10,15 Treatment-related factors associated with venous thromboembolism recurrence include a suboptimal anticoagulation quality and the insertion of a vena cava filter, 2,16 whereas thrombolysis, 17 initial therapy with lowmolecular-weight heparin (LMWH), 18 and concomitant use of statins or antiplatelet therapy may have a protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 10 studies were used. In six studies, anticoagulant treatment was short term, 36,37,[42][43][44][45] in one study long term, 40 and in three studies both long term and short term. 38,39,41 These studies contained data on 231 antithrombin-deficient individuals, of which 97 (42%) had a recurrence.…”
Section: Risk Of Recurrent Venous Thromboembolismmentioning
confidence: 99%
“…38,39,41 These studies contained data on 231 antithrombin-deficient individuals, of which 97 (42%) had a recurrence. [36][37][38][39][40][41][42][43][44][45] Out of 3,863 controls, 929 (24%) had a recurrence. The OR was 2.1; 95% CrI, 0.2 to 4.0, and the probability of the OR being >1 was 88%.…”
Section: Risk Of Recurrent Venous Thromboembolismmentioning
confidence: 99%
“…heterozygous Factor V Leiden or G20210A prothrombin mutation), it is higher for antithrombin defi ciency, combined defi ciencies, Factor V Leiden and Factor II G20210A homozygous mutation. Acquired thrombophilia is of great relevance and the risk of recurrence in patients with anti-phospholipid syndrome is twofold increased [14]. Several randomised trials and meta-analyses demonstrated that, once anticoagulant therapy has been stopped, males exhibit a risk of recurrence higher than females, with a relative risk varying from 1.3 to 3.6 [15,16].…”
Section: Individual Risk Of Recurrencementioning
confidence: 99%